Causal associations between schizophrenia and cancers risk: a Mendelian randomization study - Zhou, Kai; Zhu, Lin; Chen, Nian; Huang, Gang; Feng, Guangyong; Wu, Qian; Wei, Xiao; Gou, Xiaoxia (Frontiers in Oncology, 2023)
Background: Previous observational studies have reported inconsistent findings regarding the incidence of cancer in patients with schizophrenia compared to the general population. The causal relationship between schizophrenia and cancer remains unclear and requires further investigation. Objective: To investigate the causal relationship between schizophrenia and cancer. Methods: In this study, a two-sample Mendelian randomization (MR) analysis was conducted using publicly available genome-wide association studies to determine the causal relationship. The effect estimates were calculated using the random-effects inverse-variance-weighted method.We determined a causal relationship between genetic predisposition to schizophrenia and cancer, with schizophrenia increasing lung cancer (odds ratio (OR) = 1.0007; 95% confidence interval (CI), 1.0001-1.0013; p = 0.0192), thyroid cancer